Assessment of burned hands reconstructed with Integra® by ultrasonography and elastometry - Danin, Aurélie; Georgesco, Gabriella; Le Touze, Anne; Penaud, Alexandre; Quignon, Richard; Zakine, Gilbert (Burns, 2012)
Hand injuries have major psychological, social and professional repercussions. Treatment of burned hands is suggested to be early and optimal to avoid catastrophic consequences and allow social and professional rehabilitation. Our study analyses the long-term results obtained with Integra®, a dermal substitute used for the treatment of deep burns of the hands. A total of 29 hands were treated with Integra®. Long-term monitoring was performed on 12 hands with a clinical, ultrasonographic and elastometric study. The results were compared with those from a series of healthy hands. This study, with a low number of subjects, is a pilot report. This study showed a low complication rate, with a high percentage of engraftment of thin skin, and good cosmetic and functional quality. The thickness and viscoelasticity of the skin treated with Integra® in our series appeared to be similar to those of healthy skin. Integra® artificial skin is an attractive alternative in the treatment of deep burns of the hand and can achieve results with aesthetic and functional characteristics that are close to those of healthy skin.